UAV swarm control using low cost commercially off-the-shelf (COTS) drone - Soh, Chia Ning (Nanyang Technological University, 2021)
Unmanned aerial vehicle (UAV) swarm missions are commonly conducted using custom-made drones due to their capabilities. This project proposes equipping multiple low cost commercially off-the-shelf (COTS) drones with the ability to be simultaneously controlled and applying it to UAV swarm missions in striving to achieve a lower cost alternative to custom-made drones. The COTS drone model used in this project is the DJI Tello EDU. This report covers how control of the COTS drones is obtained using a mutual access point with a central device, and how port forwarding was used to enable simultaneous control of the drones as well as to receive unique camera feedback from every individual drone at the same time. These capabilities are applied in various drone swarm operations such as visual Simultaneous Localisation and Mapping (SLAM), facade scan for building inspection, area scanning, and drone air performances. Flight tests were conducted, showing that COTS drones were able to perform SLAM within an indoor area, a small-scale facade scan and patrol, and formation flights applicable for performances.